Pengaruh Electronic Word-of-Mouth terhadap Niat Beli pada E-commerce dengan Kepercayaan sebagai Intervening - Ayu Qirana; Ryna Parlyna; Basrah Saidani (Jurnal Bisnis, Manajemen, dan Keuangan, 2021)
This study was conducted to determine the effect of electronic word-of-mouth (eWOM) and trust on purchase intention at Shopee e-commerce. Data collection was carried out from January to July 2021 in the Greater Jakarta area. The data collection method used a survey method in the form of an online questionnaire with purposive sampling technique. The object of this research is the Greater Jakarta area society who have accessed Shopee e-commerce in the last six months. The total respondents in this study were 200 respondents consisting of 50 men and 150 women. Data analysis using SEM (Structural Equation Model) on IBM SPSS Statistics version 22 and AMOS version 21 software. The results show: electronic word-of-mouth has a positive and significant effect on trust, electronic word-of-mouth has a positive and significant effect on purchase intention, trust has a positive and significant effect on purchase intention, and electronic word-of-mouth has a positive and significant effect on purchase intention with trust as an intervening.